IEEE International Conference on Web Services (ICWS 2007) 2007
DOI: 10.1109/icws.2007.180
|View full text |Cite
|
Sign up to set email alerts
|

Transactional Coordination of Dynamic Processes in Service-Oriented Environments

Abstract: Service-oriented environments facilitate dynamic processes whose properties can be altered during runtime. The transactional support of such processes holds specific requirements that are not completely covered by existing specifications. In this paper, we introduce a life cycle model for transactional dynamic processes and analyze existing specifications with respect to their potentials to support such a model. Subsequently, we propose a framework resolving the weaknesses of existing specifications and allowi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…The prevalent role of WS-Coordination, WS-CAF and BTP has been identified by many authors who presented analyses, comparisons and enhancements of those specifications [10], [11], [12], [13]. The enhancements mostly focus on the role of the coordinator and the placement of process control in complex business processes.…”
Section: Related Workmentioning
confidence: 98%
“…The prevalent role of WS-Coordination, WS-CAF and BTP has been identified by many authors who presented analyses, comparisons and enhancements of those specifications [10], [11], [12], [13]. The enhancements mostly focus on the role of the coordinator and the placement of process control in complex business processes.…”
Section: Related Workmentioning
confidence: 98%
“…In order to cater to the new features of transactions executed by web services, various web service transaction protocols such as Business Transfer Protocol (BTP) (Ceponkus et al 2002), WS-Coordination (WS-C) (Carera et al 2005), WS-Composite Application Framework (WS-CAF) (Bunting et al 2003) had been released from OASIS (Advancing Open Standards for the Information Society). The applicability and role of these three protocols have been identified and analyzed (Kratz 2004;Little et al 2003;Husemann et al 2007) by many authors. Leymann et al (2005) identified the shortcomings of WS-C such as its inability to query the coordination state.…”
Section: Introductionmentioning
confidence: 99%